Prediction equations for 6-minute walk distance in apparently healthy Nigerians - Olufunke A. Ajiboye, MSc; Chikodi N. Anigbogu, PhD; Jane N. Ajuluchukwu, MMed; Smith I. Jaja, PhD (World Scientific Publishing, 2014)
The aims of this study were to determine the 6-minute walk distance (6MWD), establish prediction equations for the 6MWD in apparently healthy Nigerians, evaluate any effects regarding participant sex, and compare measured 6MWDs with the predicted 6MWD from reference equations derived from other populations. Four hundred and twenty two (422) apparently healthy Nigerians participated in the study. The 6-minute walk test was carried out according to the American Thoracic Standard-standardized protocol. The 6MWD obtained from the study was compared with reference values from other foreign populations. There were no significant differences between the mean age and mean weight of the male and female participants. However, significant difference existed in the mean height and mean body mass index (BMI; p < 0.001) of these participants. Male participants covered a statistically significant longer distance than female participants (p < 0.001). The mean 6MWD measured in Nigerian participants (517.6 ± 72.2 m) was statistically lower than 6MWD in Americans, Brazilians, and Tunisians and was higher than in Arabians (p ≤ 0.002), respectively. The 6-MWD in healthy Nigerians cannot be predicted by established reference equations from other populations. The regression equations established in this study may better predict the distance for Nigerians.